Pengembangan Media Video Pembelajaran pada Mata Pelajaran Informatika Materi Jaringan Komputer dan Internet Kelas VII SMP - Fitriani, Vina; Eldarni, Eldarni; Novrianti, Novrianti; Yusri, Meldi Ade Kurnia (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop a learning video media for the subject of Informatics, particularly on the topic of Computer Networks and Internet for grade VII of junior high school. This development is in response to the lack of varied media in learning which often leads to boredom and low student comprehension. This research employs a Research & Development (R&D) approach using the 4D development model, which consists of four stages: define, design, develop, and disseminate. The results of the study show that the average validation score by the material expert was 4.78, categorized as “very valid”. Validation by media expert 1 yielded an average score of 4.95 (“very valid”), while media expert 2 gave an average score of 4.035 (“valid”). Furthermore, a practicality test involving 25 students resulted in an average score of 4.84, indicating a “very practical” category. Based on these findings, the video-based learning media on Computer Networks and the Internet for Grade VII is considered feasible and appropriate for use in the learning process.